Pengaruh Efikasi Diri Kewirausahaan Terhadap Niat Berwirausaha Pada Generasi Z Di Jawa Barat - Sopianti, Sopi; Sarah, Ira Siti; Fujiasti, Sherry Novalia (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
The research investigates the impact of digital marketing training on the entrepreneurial intention through the mediating role of self-efficacy among Generation Z (19 – 24 years old) in West Java. The aims of study to analyze how digital marketing training directly and indirectly through self-efficacy to influence entrepreneurial intention of Generation Z. The method of study using quantitative approach was applied, with data collected using google forms with data analysis techniques descriptive statistics, classical assumption testing, path analysis, and hypothesis testing using IBM SPSS Statistics 26. The sample comprises 400 respondents who have participated in digital marketing training conducted by either government agencies or non-governmental organizations, selected through purposive sampling combined with stratified random sampling. The finding of study that digital marketing training has a positive influence on self-efficacy and entrepreneurial intention, with self-efficacy mediating the relationship between digital marketing training and entrepreneurial intention. Based on the finding, the study has directly and indirectly effect. This study is limited to Generation Z (aged 19-24 years) in West Java, which restricts the generalizability of the findings. However, the implications of this study can serve as a foundation for practitioners, policymakers, or academics in making informed decisions or taking relevant actions. Keywords: Digital Marketing Training, Self-Efficacy, Entrepreneurial Intention